2011
DOI: 10.1364/oe.19.026044
|View full text |Cite
|
Sign up to set email alerts
|

Dark-field digital holographic microscopy for 3D-tracking of gold nanoparticles

Abstract: We present a new technique that combines off-axis Digital Holography and Dark Field Microscopy to track 100nm gold particles diffusing in water. We show that a single hologram is sufficient to localize several particles in a thick sample with a localization accuracy independent of the particle position. From our measurements we reconstruct the trajectories of the particles and derive their 3D diffusion coefficient. Our results pave the way for quantitative studies of the motion of single nanoparticle in comple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 36 publications
5
44
0
Order By: Relevance
“…All the driving signals are synchronized by a common 10 MHz clock. Figure 2 illustrates our reconstruction procedure [4,5] with non-Doppler shifted images. We have considered here four phase holograms: H = (I 0 − I 2 ) + j(I 1 − I 3 ) (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All the driving signals are synchronized by a common 10 MHz clock. Figure 2 illustrates our reconstruction procedure [4,5] with non-Doppler shifted images. We have considered here four phase holograms: H = (I 0 − I 2 ) + j(I 1 − I 3 ) (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The reconstruction procedure is similar to the one used in previous works [50,51]. To illustrate reconstruction, let us consider 4 phase detection of the ballistic peak signal (no Doppler shift).…”
Section: Spatial Filtering and Reconstructionmentioning
confidence: 99%
“…Another study using digital holography showed that using dark field excitation could enable visualization of gold nanoparticles without the need for photothermal excitation [49]. Here the nanoparticles were excited with darkfield illumination and the scattered light was imaged with on axis holography.…”
Section: Digital Holographymentioning
confidence: 99%